Intrauterine and early postnatal exposure to outdoor air pollution and lung function at preschool age. Issue 1 (20th October 2014) - Morales, Eva; Garcia-Esteban, Raquel; de la Cruz, Oscar Asensio; Basterrechea, Mikel; Lertxundi, Aitana; de Dicastillo, Maria D Martinez López; Zabaleta, Carlos; Sunyer, Jordi
Abstract : Background: Effects of prenatal and postnatal exposure to air pollution on lung function at preschool age remain unexplored. We examined the association of exposure to air pollution during specific trimesters of pregnancy and postnatal life with lung function in preschoolers. Methods: Lung function was assessed with spirometry in preschoolers aged 4.5 years (n=620) participating in the INfancia y Medio Ambiente (INMA) cohort. Temporally adjusted land use regression (LUR) models were applied to estimate individual residential exposures to benzene and nitrogen dioxide (NO2 ) during specific trimesters of pregnancy and early postnatal life (the first year of life). Recent and current (1 year and 1 week before lung function testing, respectively) exposures to NO2 and nitrogen oxides (NOx ) were also assessed. Results: Exposure to higher levels of benzene and NO2 during pregnancy was associated with reduced lung function. FEV1 estimates for an IQR increase in exposures during the second trimester of pregnancy were −18.4 mL, 95% CI −34.8 to −2.1 for benzene and −28.0 mL, 95% CI −52.9 to −3.2 for NO2 . Relative risk (RR) of low lung function (<80% of predicted FEV1 ) for an IQR increase in benzene and NO2 during the second trimester of pregnancy were 1.22, 95% CI 1.02 to 1.46 and 1.30, 95% CI 0.97 to 1.76, respectively. Associations for early postnatal, recent and current exposures were not statistically significant. Stronger associations appeared among allergic children and those of lower social class. Conclusions: Prenatal exposure to residential traffic-related air pollution may result in long-term lung function deficits at preschool age.